Rainfall and Temperature Analysis for Predicting Drought-Prone Areas in Tangerang Regency - Oktarina, Silsa Dwi; Ruhiat, Yayat; Oktarisa, Yuvita (Lensa: Jurnal Kependidikan Fisika, 2025)
Drought has emerged as a critical issue in Tangerang Regency, Banten Province, primarily driven by the prolonged dry season, declining rainfall, and rising temperatures above average, all of which are exacerbated by the El Niño phenomenon. These conditions pose serious threats, including water shortages, reduced agricultural productivity, and the potential for widespread drought if left unaddressed. This study aims to map drought threat levels at the sub-district scale based on rainfall and temperature parameters. The integration of these two variables is essential, as drought is influenced not only by insufficient rainfall but also by elevated temperatures. Thus, a multivariable approach offers a more comprehensive and accurate spatial assessment. The analysis applied in this study involves scoring and overlay techniques for each contributing parameter. The results identify areas with varying degrees of drought threat—low, light, moderate, high, and extreme. Notably, 27.63% of the regency is classified under extreme drought risk, predominantly in the central to southern regions, due to the combination of very low rainfall and very high temperatures. The resulting drought threat map serves as a crucial reference for local governments, farmers, and the Regional Disaster Management Agency (BPBD) in planning effective mitigation strategies, early warning systems, and sustainable water resource management.